2009
DOI: 10.4049/jimmunol.0803847
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Intercross Line Mapping Suggests That Ncf1 (Ean6) Regulates Severity in an Animal Model of Guillain-Barré Syndrome

Abstract: We here present the first genetic fine mapping of experimental autoimmune neuritis (EAN), the animal model of Guillain-Barré syndrome, in a rat advanced intercross line. We identified and refined a total of five quantitative trait loci on rat chromosomes 4, 10, and 12 (RNO4, RNO10, RNO12), showing linkage to splenic IFN-␥ secretion and disease severity. All quantitative trait loci were shared with other models of complex inflammatory diseases. The quantitative trait locus showing strongest linkage to clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…We used linkage analysis of an advanced intercross line (AIL) made between MHC-identical (including the TNF locus) DA and PVG.AV1 rat strains to define a genetic region regulating TNF production after LPS stimulation. Our work focused on a region of rat chromosome 4 known to regulate several inflammatory diseases, including experimental autoimmune encephalomyelitis (EAE) (20), collagen-induced arthritis (CIA) (21), pristaneinduced arthritis (PIA) (22), and experimental autoimmune neuritis (23). We identified a quantitative trait locus (QTL) using the 12th generation of the AIL and confirmed our findings using congenic rats that captured the biological phenotype.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…We used linkage analysis of an advanced intercross line (AIL) made between MHC-identical (including the TNF locus) DA and PVG.AV1 rat strains to define a genetic region regulating TNF production after LPS stimulation. Our work focused on a region of rat chromosome 4 known to regulate several inflammatory diseases, including experimental autoimmune encephalomyelitis (EAE) (20), collagen-induced arthritis (CIA) (21), pristaneinduced arthritis (PIA) (22), and experimental autoimmune neuritis (23). We identified a quantitative trait locus (QTL) using the 12th generation of the AIL and confirmed our findings using congenic rats that captured the biological phenotype.…”
supporting
confidence: 55%
“…With clinical differences in EAE and PIA but not CIA, it seems that T cells may be an important component determining disease severity (47,48), as the role of B cells and Abs in CIA is more relevant (49). In addition, IFN-g levels in T cells are regulated during experimental autoimmune neuritis by the same locus, which argues for adaptive immune system regulation (23). At the same time, the proinflammatory macrophage phenotype in DA rats would indicate their role as effector cells contributing to disease severity through damaging MMP expression as well as recruitment of other cells through chemokine release.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has been shown to act by increasing the phagocyte oxidative burst in vivo [61]. In an acute model of Guillain Barré, phytol treatment led to a strong reduction in experimental allergic neuritis disease severity and a lower number of IFN-c-secreting cells in late disease stage [58]. The fact that phytol is an oil makes it an unlikely candidate for development by the pharmaceutical industry because of challenging SAR, pharmacokinetics, and metabolism.…”
Section: Phytolmentioning
confidence: 99%
“…Indeed, an insufficient ROS production by systemic antigen presenting cells, such as mononuclear phagocytes, will favor autoimmune neuroinflammation. Genetic studies identified a polymorphism in the Ncf1 gene coding for p47 phox , a regulatory cytosolic factor of NOX-dependent oxidant production, which is associated with susceptibility in rheumatoid arthritis models and other autoimmune disorders [116], including experimental allergic encephalomyelitis, an animal model of multiple sclerosis (MS) [62], and experimental allergic neuritis, a model of Guillain Barré syndrome [58]. The link between Ncf1 and disease susceptibility was further confirmed in humans because circulating leukocytes of patients affected by MS [110] and other autoimmune neuropathies [109] have a lower capacity for ROS generation.…”
mentioning
confidence: 99%
“…We recently reported a QTL governing tumour necrosis factor (TNF) production in rats through the regulation of a multitude of immune response genes and macrophage activation phenotypes [7]. The QTL also regulates susceptibility to multiple immune-mediated diseases including experimental autoimmune encephalomyelitis (EAE) [8], collagen-induced arthritis [9], pristine-induced arthritis [10], and experimental autoimmune neuritis [11]. To identify a candidate gene we hypothesized that the regulator would control many genes in the immune system because of multiple affected genes.…”
Section: Introductionmentioning
confidence: 99%